PERAN BIMBINGAN KONSELING PENDIDIKAN ISLAM DALAM MEMBENTUK AKHLAK PESERTA DIDIK DI MADRASAH TSANAWIYAH - Rambe, Mirza Syahdat; Hakam, Abdillah; Zaira, M. Firas Samudera; Hamid, Abdul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The complexity of students' moral and psychological challenges in the modern era demands integrative educational services. This study aims to analyze the strategic role of Islamic Education in the implementation of Islamic Guidance and Counseling (BKPI) and its contribution to the formation of students' morals in Islamic Junior High Schools (Madrasah Tsanawiyah). Using a descriptive qualitative approach, the study involved counselors and students as subjects, with data collection through observation, in-depth interviews, and documentation. Analysis was carried out systematically, starting from data reduction to drawing conclusions. The findings indicate that the implementation of BKPI based on Islamic values, such as faith and morals, through a humanist-religious approach has proven effective in shaping students' personalities. Counselors who act as good role models are able to instill the values ​​of honesty, patience, and responsibility, thus positively impacting students' religious discipline and emotional control. Despite technical obstacles such as time constraints, the counseling approach based on the Qur'an and Hadith successfully creates psychological calm and corrects deviant behavior. The main conclusion confirms that the substantial integration of Islamic Education Science in BKPI services is crucial to produce a generation that is not only intellectually intelligent, but also has spiritual maturity and noble character in facing the dynamics of life. ABSTRAK Kompleksitas tantangan moral dan psikologis siswa di era modern menuntut layanan pendidikan yang integratif. Penelitian ini bertujuan menganalisis peran strategis Ilmu Pendidikan Islam dalam pelaksanaan Bimbingan dan Konseling Pendidikan Islam (BKPI) serta kontribusinya terhadap pembentukan akhlak peserta didik di Madrasah Tsanawiyah. Menggunakan pendekatan kualitatif deskriptif, penelitian melibatkan konselor dan siswa sebagai subjek, dengan pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Analisis dilakukan secara sistematis mulai dari reduksi data hingga penarikan kesimpulan. Temuan menunjukkan bahwa implementasi BKPI yang berlandaskan nilai-nilai Islam, seperti akidah dan akhlak, melalui pendekatan humanis-religius terbukti efektif membentuk kepribadian siswa. Konselor yang berperan sebagai uswah hasanah mampu menanamkan nilai kejujuran, kesabaran, dan tanggung jawab, sehingga berdampak positif pada peningkatan kedisiplinan ibadah dan kontrol emosi siswa. Meskipun terdapat kendala teknis seperti keterbatasan waktu, pendekatan konseling berbasis Al-Qur’an dan Hadis berhasil menciptakan ketenangan psikologis dan memperbaiki perilaku menyimpang. Simpulan utama menegaskan bahwa integrasi substansial Ilmu Pendidikan Islam dalam layanan BKPI sangat krusial untuk mencetak generasi yang tidak hanya cerdas intelektual, tetapi juga memiliki kematangan spiritual dan berakhlakul karimah dalam menghadapi dinamika kehidupan.